The Effect of Capital Structure and Good Corporate Governance on Financial Performance With Agency Cost as a Control Variable : (Case Study on Manufacturing Companies in the Consumer Goods Industry Sector Listed on Idx For 2016-2020 Period) - Agus Dwi Sasono; Leni Septiana (NAROTAMA UNIVERSITY, Indonesia, 2022)
This study aims to test and analyze empirically the effect of capital structure, independent board of commissioners, institutional ownership and managerial ownership on financial performance with agency cost as a control variable in manufacturing companies in the consumer goods industry sector listed on the IDX. This study uses a quantitative research method that is descriptive of explanation. The population in this study were 73 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2016-2020 period and the final sample processed in this study were 7 companies which were taken through purposive sampling technique. Data analysis techniques used include descriptive statistical analysis, classical assumption test and multiple linear regression. Hypothesis testing using t-test with an alpha significance level of 5%. From the results of data processing using SPSS, it is found that the coefficient value (t test) shows the capital structure variable (X1) with a t-value of 0.001 which means that the capital structure affects the company's financial performance. The independent board of commissioners (X2) with a t-value of 0.023 which means that the independent board of commissioners has an effect on the company's financial performance. Meanwhile, institutional ownership (X3) and managerial ownership (X4) have no effect on financial performance as evidenced by the t-values ??of 0.415 and 0.566. Simultaneously, capital structure, independent board of commissioners, institutional ownership and managerial ownership affect financial performance with agency cost as a control variable.